2022
DOI: 10.3390/jof8090899
|View full text |Cite
|
Sign up to set email alerts
|

Evidencing New Roles for the Glycosyl-Transferase Cps1 in the Phytopathogenic Fungus Botrytis cinerea

Abstract: The fungal cell wall occupies a central place in the interaction between fungi and their environment. This study focuses on the role of the putative polysaccharide synthase Cps1 in the physiology, development and virulence of the grey mold-causing agent Botrytis cinerea. Deletion of the Bccps1 gene does not affect the germination of the conidia (asexual spores) or the early mycelial development, but it perturbs hyphal expansion after 24 h, revealing a two-phase hyphal development that has not been reported so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In the fungal pathogen B. cinerea , the GT2 family contributes to the biogenesis and remodeling of the cell wall. This family contains the synthases for production of chitin, which plays a structural role in the fungal cell wall (Blandenet et al ., 2022). In our analysis, we observe expansion of gene families of AB hydrolases (OG0006140), glycoside hydrolase family 1 (OG0006802), and the alpha-mannosyltransferase protein (OG0007561), which may be involved in cell wall modifications in response to cold temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In the fungal pathogen B. cinerea , the GT2 family contributes to the biogenesis and remodeling of the cell wall. This family contains the synthases for production of chitin, which plays a structural role in the fungal cell wall (Blandenet et al ., 2022). In our analysis, we observe expansion of gene families of AB hydrolases (OG0006140), glycoside hydrolase family 1 (OG0006802), and the alpha-mannosyltransferase protein (OG0007561), which may be involved in cell wall modifications in response to cold temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of rseA/cpsA affects hyphal growth and morphogenesis of A. nidulans and its secondary metabolite and extracellular enzyme production 15,26 . Recently, it was reported that rseA/cpsA orthologs influence plant and human pathogens 30,32,35 . Since deletion of rseA or its ortholog in N. crassa affects cell wall composition and causes hyperactivation of the CWI pathway, it has been proposed that RseA and its ortholog play a role in cell wall biogenesis 15,26,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic interactions between hosts and pathogens result in positive selection on proteins responsible for pathogenesis/virulence. In this study, we identified four proteins with signatures of selection (SCB64107.1, SCB65560.1, CEF85567.1, CEF79590.1), which have been shown to contribute to pathogenicity/virulence in different fungal pathogens such as: Sclerotinia sclerotiorum [59], Verticillium dahliae [60], Aspergillus flavus [61], Magnaporthe grisea [62], Botrytis cinerea [65], Candida albicans and Cryptococcus neoformans [66]. Among them, only one (SCB65560.1), to date, has been previously reported to be involved in virulence of F. graminearum [63].…”
Section: Discussionmentioning
confidence: 99%